2022
DOI: 10.3389/fcimb.2022.928578
|View full text |Cite
|
Sign up to set email alerts
|

The Gastrointestinal Load of Carbapenem-Resistant Enterobacteriacea Is Associated With the Transition From Colonization to Infection by Klebsiella pneumoniae Isolates Harboring the blaKPC Gene

Abstract: BackgroundHealthcare-associated infections by carbapenem-resistant Klebsiella pneumoniae are difficult to control. Virulence and antibiotic resistance genes contribute to infection, but the mechanisms associated with the transition from colonization to infection remain unclear.ObjectiveWe investigated the transition from carriage to infection by K. pneumoniae isolates carrying the K. pneumoniae carbapenemase–encoding gene blaKPC (KpKPC).MethodsKpKPC isolates detected within a 10-year period in a single tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(50 reference statements)
0
6
0
2
Order By: Relevance
“…ST11 is a monolocus variant of ST258 within the same clonal complex, 39 which is considered to be responsible for the global spread of KPC over the past 20 years, with KPC-2 and KPC-3 being the dominant subtypes. 40 Therefore, our study concluded that carbapenemase types were closely related to specific STs and that the risk of BSI in KPC-carrying K. pneumoniae rectal carriers was much higher than in NDM-carrying K. pneumoniae carriers. While our molecular results support the association between CRKP colonization and BSI, suggesting that hospitalized patients are infected with their colonized strains, our study highlights the importance of screening for specific carbapenemase types with rectal colonization.…”
Section: Discussionmentioning
confidence: 70%
“…ST11 is a monolocus variant of ST258 within the same clonal complex, 39 which is considered to be responsible for the global spread of KPC over the past 20 years, with KPC-2 and KPC-3 being the dominant subtypes. 40 Therefore, our study concluded that carbapenemase types were closely related to specific STs and that the risk of BSI in KPC-carrying K. pneumoniae rectal carriers was much higher than in NDM-carrying K. pneumoniae carriers. While our molecular results support the association between CRKP colonization and BSI, suggesting that hospitalized patients are infected with their colonized strains, our study highlights the importance of screening for specific carbapenemase types with rectal colonization.…”
Section: Discussionmentioning
confidence: 70%
“…Gastrointestinal carriage of AMR bacteria may precede infection and, without active surveillance, can serve as a hidden reservoir for drug-resistant organisms' transmission in hospital environments [11] [12] [13]. Yet, few studies have focused on faecal carriage of MDR bacteria and risk factors for colonization in Kenya, including faecal carriage of CRE in adults and children (1%) [14], carbapenemase-producing organisms (62.4%) in hospitalized newborns [15], and ESBL Enterobacteriales among neonates before (10%) and after admission (55%) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the degree of intestinal colonization by opportunistic pathogens, especially ESBL- and carbapenemase-producers, can have a direct effect on infection and mortality rates ( Dahdouh et al., 2021 ; Migliorini et al., 2022 ; Pérez-Nadales et al., 2022 ). Moreover, this colonization can be occult, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…present at such low amounts that it is not detected by traditional culture media, but has the potential to quickly expand and dominate the intestinal microbiome in response to antibiotic pressure ( Sim et al., 2022 ). Previous studies have shown associations between high intestinal Relative Loads (RLs) of carbapenemase-producing Klebsiella pneumoniae , antibiotic consumption, and development of infections in hospitalized adult patient populations ( Migliorini et al., 2022 ;, Lázaro-Perona et al., 2020 ), and in pediatric liver transplant patients ( Dahdouh et al., 2022 ). The aim of this study is to use the qPCR assay developed and validated in these previous studies to determine the relationship between the intestinal RLs of selected ESBL and carbapenemase genes, antibiotic consumption, occult colonization, gut microbiome dysbiosis, and extra-intestinal spread of MDROs among critically ill pediatric patients.…”
Section: Introductionmentioning
confidence: 99%